Dissemination of the Activities of the Lithuanian Language Society and Other Similar Non-governmental Organizations in the Periodical “Gimtoji Kalba” - Rita Urnėžiūtė (Lietuvių Kalba)
After the restoration of Lithuania’s independence in 1990, non-governmental organizations devoted to the linguistic education, the teaching of the Lithuanian language and its popularisation, and the rights of the state language, that had been active during the interwar period, began to be re-established. The most prominent of the organizations restored were the Lithuanian Language Society and the Union of Teachers of Lithuanian Language and Literature. During the years of the restored independence, various new organizations emerged whose aims and activities had more or less in common with those of the Lithuanian Language Society and the Union of Teachers of the Lithuanian Language and Literature.